COVID-19 in Women's health reducing the risk of infection to patients and staff during acute and elective hospital admission for gynaecological surgery. (June 2021) - Odejinmi, Funlayo; Egbase, Elizabeth; Clark, T. Justin; Mallick, Rebecca
Abstract: The novel coronavirus SARS-Cov-2 has changed healthcare on a worldwide scale. This highly contagious respiratory virus has overwhelmed healthcare systems. Many staff were redeployed, and there was widespread cessation of non-urgent outpatient clinics and surgery. Outpatient clinics and theatre areas were converted to COVID-19 wards and intensive care units. Following the first peak, services began to recommence with new triaging and prioritisation guidance to safeguard patients and staff. Different countries and healthcare systems produced differing guidance and, in particular, variation in the best approach to continuing acute and elective surgical procedures. This chapter collates and evaluates the increasing international literature concerning the surgical management of gynaecological conditions during the pandemic, such that clear inferences, recommendations and guidance can be generated to aid clinical practice and safeguard against further major disruption arising from further COVID-19 peaks. The available data are assessed within the context of the current phase of the COVID-19 pandemic.